Xanthan gum and Tara gum galactomannans have a synergistic effect on gelation properties. Issue 2 (May 2023) - Huamaní-Meléndez, Víctor Justiniano; Mauro, Maria A; Darros-Barbosa, Roger
Rheology is essential for assessing the applicability of bio-based and renewable polymers because it provides crucial information about their mechanical properties, flow behavior, and processing characteristics. So, gels formed by carbohydrate polymer mixtures have specific rheological properties that can be used in the food industry to improve processes, develop new products, or replace ingredients. The aim of the research was to characterize the interactions and synergy of the aqueous mixture of Xanthan gum (XG) and Tara gum (TG). Commercial TG was previously purified, and aqueous mixtures were prepared using varying concentrations of XG and TG. Rheological properties were determined using a rotational rheometer. An equation was proposed to quantify the degree of solid behavior of the formed gel as a function of its mechanical properties. Pure TG or XG in aqueous solution exhibited pseudoplastic behavior. At a 0.4% w/w concentration, the XG solution displayed a "weak gel" behavior. The concentrations of XG and TG in the aqueous mixture of the gums had a significant effect on the gel strength, presenting a region of maximum value, limited between the concentrations of 0.4–0.5% TG and 0.2–0.3% XG. The greatest strength of the gel was obtained at intermediate concentrations of gum; however, the value of the strain limit displayed a linear increase with TG concentration, confirming the synergistic effect on the solid-like behavior and strength of the gel.